Management of Modification of Regional Typical Food "Pepes" to Develop an Entrepreneurial Spirit by Utilizing Digital Technology - Niraviona, Franselin Puspita Ester; Putri, Nadia Septian (JENTIK : Jurnal Pendidikan Teknologi Informasi dan Komunikasi, 2023)
The research entitled "Management of Modifications of Regional Typical Food "Pepes" to Develop an Entrepreneurial Spirit by Utilizing Digital Technology" is motivated by the rapid development of the culinary world and high interest from the community. The community began to look for modified regional specialties but did not eliminate the taste and characteristics of the food. This research was conducted through descriptive interpretative research that aims to identify community interest in regional specialties: (1) Modification of traditional food made from fish, chicken and tofu + mushrooms, (2) Community perceptions of traditional food. The earliest data collection methods are observation, interviews and documentation, while the theoretical basis used is the theory of perception and marketing strategy. The modification process that serves traditional regional food from fish has several modifications from the essential ingredients, namely Pepes chicken and Pepes tofu + mushrooms, for process modifications such as (1) Seasoning, (2) Processing, and (3) Packaging. The community has a positive perception of traditional food made from fish, chicken and tofu + mushrooms. Based on the research results, a suitable effort to be developed is to look at the existing constraints combined with the advantages that exist in traditional food offered to the community as an effort to develop food products made from fish, chicken, tofu + mushrooms in terms of seasoning, processing, taste, presentation, and menu variations.